The Comparison between perspective of doctors, nurses and patients - Jafari manesh, Hadi; Zagheri Tafreshi, Mans0reh; Ashktorab, Tahereh; Alavi Majd, Hamid (Advances in Nursing & Midwifery, 2012)
ABSTRACT Background and aim: Patient advocacy is one of the most controversial issues in nursing during recent two decades. The purpose of this study was to determine perspective of doctors, nurses and patients towards the advocacy role of nurses about patients in hospitals affiliated to Shahid Beheshti University of Medical Sciences. Materials and Methods: This descriptive- comparative study was conducted on a sample of 329 doctors and 345 nurses and 225 patients, selected by a multi-stage sampling method. Data were collected using a demographic questionnaire and a Nursing-Advocacy-Perspective-Scale. The content and construct validity as well as internal consistency and test-retest reliability method were assessed and confirmed beforehand. The data was analyzed using SPSS 16 and statistical tests at the significant level of P<0.05. Results: There was a significant difference between the three groups in average scores perspective (p<0/05). Average scores of patients were higher than nurses and doctors, and nurses average scores was significantly higher than physician (p<0/05). Conclusion : The nurse managers should promote the role of the facilitator and prevent loss of nursing advocacy and creating opportunities to provide this role in hospitals. In this regard the views of interest groups may help. Key Words: perspective, nursing advocacy, doctors, nurses, patie REFERENCES - Lavoie M Valois P et al (2000). The attitude of Canadian nurse towards advanced directives. Nursing Ethics.7 (5) 399-411. -Chafey K Rhea M Shannon AM et al (1998). Characterization of advocacy by practicing nurses. Journal of Professional Nursing.14 (1) 43-52. -Davis A Davis AJ Konishi E Tashiro M (2003). A pilot study of selected Japanese nurses idea on patient advocacy. Nursing Ethics. 10 (4) 404- 413. -Dobrowolska B Wro ska I Fidecki W et al (2007). Moral obligations of nurses bused on the ICN, UK, Irish and Polish codes of ethics for nurses. Nursing Ethics. 14 (2) 171-180. -Ebrahimi H et al (2006). Prevent harm to the patient or damage to the nurse: Nurses’ ethical conflicts in the area of ethical decision-making. Journal of Zanjan University of Medical Sciences. 4 (57) 45-56. (Persian) -Fry ST Megan-Jane J (2002). Ethics in Nursing Practice: A Guide to Ethical Decision Making. Oxford: Blackwell Science. -Hanks RG (2008). The lived experience of nursing advocacy: a descriptive pilot study. Nursing Ethics.15 (4) 468-477. -Hanks RG (2010). Development and testing of an instrument to measure protective nursing advocacy. Nursing Ethics.17 (2) 255-267. -Hellwig SD Yam M DiGiulio M (2003). Nurse case managers’ perception of advocacy: a phenomenological inquiry. Case Management. 8 (2) 53-63. 59/ ... # 0,C ! " - 0- -Joulaee S (2007) . Explain the emergence of patient rights. PhD Dissertation of Nursing Education. Nursing and Midwifery School. Tehran University of Medical Sciences.Tehran, Iran. (Persian) -Karimi R Dehghan nairi N Daneshvari ameri Z et al (2008). Comparing Attitudes of Nurses and inpatient Adolescents about Patient’s Dignity. Journal of Medical Ethics and History. 1 (4) 53-62. (Persian) -Karro J Dent AW Farish S (2005). Patient perception of privacy infringement in an emergency depart ent. Emergency Medicine Australasia. 17 (2) 117-123. -Kazem Nejad A Heidari MR Norouz zadeh R at al (2010). Statistical Methods in Health Care Research and Using SPSS in Data Analysis. First Edition. Tehran. Salemi-Jame Negar Publisher. (Persian) -Kubsch SM Sternard MJ Hovarter R et al (2004). A holistic model of advocacy: factor that influence its use. Complementary Therapies in Nursing and Midwifery.10 (1) 37-45. -Mallik M (1997). Advocacy in nursing- perception nurses. Journal of Clinical Nursing. 6 (4) 303- 313. -Marakou K Dalla-Vorgia P Garanis-Papadatos T et al. (2001). Satisfying patients rights: a hospital patient survey. Nurse Ethics. 8 (6) 499-509. -McGrath A Walker A (1999). Nurse’s perception and experience of advocacy. Contemporary Nurses.8 (3) 72-78. -Munro BH (2005) Statistical Methods for Health Care Research. 5 th Edition. Philadelphia. Lippincott. Williams and welkins. -Nahigian E (2003). Factor associated with the advocacy decisions of registered professional nurses employed as staff nurses in inpatient adult care hospitals. Dissertation for Degree of Doctor of Nursing Science. Faculty of the School of Nursing: University at Buffalo: The State University of New York.USA. [Online]. < http://www.proquest.com >. [24 March 2010] -Negarandeh R (2005). Nursing and Patient advocacy: A Grounded Theory. PhD Dissertation in Nursing. Nursing and Midwifery School. Iran University of Medical Sciences. Tehran, Iran.(Persian) -Negarandeh R Oskoii F Ahmadi F et al (2005a). Patient advocacy properties. Journal of Zanjan University of Medical Sciences.13 (53) 29-38. (Persian) -Negarandeh R Oskoii F Ahmadi F et al (2005b). Nurses Experiences of Facilitators and Inhibitors in Patient advocacy. Journal of Iran University of Medical Sciences.12 (47) 175-186. (Persian) -O’Connor T and Kelly B (2005). Bridging the gap: a study of general nurses perceptions’ of patient advocacy in Ireland. Nursing Ethics.12 (5) 453-467. -Parsapoor A et al (2010). Survey of patients, nurses and doctors attitude to regarding of cods of patients’ right in Tehran University of Medical Sciences Hospitals. Journal of Medical Ethics and History 3(1) 53-64. (Persian) -Rezaei Kargar F (2005). Advocacy: an important role for a nurse. Journal of Faculty of Nursing & Midwifery of Shaheed Beheshti.15 (48)11-19. (Persian) -Rushton CH (1995). Creating an ethical practice environment. Critical Care Nurse Clinics of North America.7 (2) 384- 397. -Sellin SC (1995). Out of a limb: a qualitative study of patient advocacy in institutional nursing. Nursing Ethics.2 (1) 19-29. -Shakeri-nia A (2009). Relationship Between doctor-patient and its role in satisfaction the patients’ treatment. Journal of Medical Ethics and History.2 (3) 9-16. (Persian) -Snowball J (1996) Asking nurse about advocacy for patients "reactive" and "proactive" accounts. Journal of Advanced Nursing.24 (2) 67-75. -Sundin-Huard D and Fahy k (1999). Moral distress, Advocacy and burnout: theorizing the relationships. International Journal of Nursing Practice.5 (1) 8-13. -Vaartio H Leino-Kilpi H Suominen T et al. (2008). The content of advocacy in procedure pain care- patient and nurses perspective . Journal of Advanced Nursing. 64 (5) 504-513. -Vanaki Z (2002). Nursing support and its effect on satisfaction in cancer patients undergoing chemotherapy. PhD Dissertation of Nursing. Faculty of Nursing and Midwifery: Tarbiat Modares University.Tehran, Iran. (Persian) -Voskoii-ashkori kh (2008). [Evaluation of respected to patients’ rights in hospitals affiliated to Tehran University of Medical Sciences]. Journal of Medical Ethics and History.2 (4) 47-53. (Persian) ... /5 ! = "E1P " 5 1391 ,& 77 / 22 ! /10 -Walsh K Kowanko I (2002). Nurse and patient perception of dignity. International Journal Practice. 8 (3)143-145. -Wheeler P (2000). Is advocacy at the heart of professional practice?. Nurse Standard.14 (36) 39-41. -Yaghmaei F (2009). Measuring Behavior in Research by Valid and Reliable Instruments. 2 nd Edition. Tehran. Publications of Shaheed Behshti Medical Sciences. (Persian) -Zokaie Yazdi S Mosaib Moradi J Mehran A et al (2002). Perspective of the nursing staff at hospitals affiliated to the Tehran University of Medical Sciences about the roles and activities of the nurses. Journal of Nursing and Midwifery. Tehran University of Medical Sciences (Hayat).16 (8)22-32. (Persian) Birrell J Thomas D Jones CA (2006). Promoting privacy and dignity for older patients in hospital. Nursing Standard. 20 (18) 41-46. -Blondeau D